Les classes populaires aussi quittent Bruxelles. Une analyse de la périurbanisation des populations à bas revenus - Sarah De Laet (Brussels Studies, 2018)
Residential movements from the territory of the Brussels-Capital Region to suburban municipalities in Flanders and Wallonia have usually been studied from the angle of the middle classes. However, today, 30 % of people who leave the Region to live elsewhere in Belgium are part of the working classes. The urban working classes are subject to dual pressure: social, on the one hand, with the destructuring of the salary model, the shortage of jobs and economic insecurity; and spatial, on the other hand, in particular due to the increase in the cost of housing in the city. Faced with this pressure, certain working-class households have chosen to move outside the Brussels-Capital Region. Following the works which drew attention to these processes of “modest suburbanisation” in particular in France, this article focuses on the significance of this phenomenon in the case of Brussels. It also highlights the places of destination of the working-class households which leave the central working-class neighbourhoods of Brussels. From the point of view of the latter, the movements towards the municipalities on the nearby outskirts or other cities result in a sort of social and spatial selection with significant implications for the places they are leaving.